2022
DOI: 10.7759/cureus.28913
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed Radiofrequency for Postherpetic Trigeminal Neuralgia: A Case Report

Abstract: Trigeminal postherpetic neuralgia has been reported to cause chronic headaches and facial pain. There are various modalities of treatment ranging from pharmacological to surgical treatment. However, these are frequently accompanied by undesirable side effects and minimal efficacy. Pulsed radiofrequency has been used to treat chronic pain but it is often seen as an unconventional treatment for postherpetic neuralgia. Nonetheless, the literature supports its use for alleviating pain with minimal complications. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…All treatments in patients of the PRF group were ultrasoundguided, and the supraorbital nerve could innervate the frontofacial region through the supraorbital foramen or supraorbital notch out of the eyebrow arch, which is the anatomical basis for treating frontofacial PHN (Figure 2). Javier et al used ultrasound-guided PRF of the infraorbital nerve to treat the second branch of PHN and reported that the structures around the nerve and blood vessels were observable under ultrasound, which facilitated avoiding of blood vessels (6); however, only one case was enrolled in this study, whereas studies on ultrasound-guided PRF of the supraorbital nerve are lacking. Using high-frequency ultrasound scanning, we found that the hyperechoic bone was interrupted by the supraorbital foramen or notch and observed the supraorbital artery, which provided a theoretical basis for our study.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…All treatments in patients of the PRF group were ultrasoundguided, and the supraorbital nerve could innervate the frontofacial region through the supraorbital foramen or supraorbital notch out of the eyebrow arch, which is the anatomical basis for treating frontofacial PHN (Figure 2). Javier et al used ultrasound-guided PRF of the infraorbital nerve to treat the second branch of PHN and reported that the structures around the nerve and blood vessels were observable under ultrasound, which facilitated avoiding of blood vessels (6); however, only one case was enrolled in this study, whereas studies on ultrasound-guided PRF of the supraorbital nerve are lacking. Using high-frequency ultrasound scanning, we found that the hyperechoic bone was interrupted by the supraorbital foramen or notch and observed the supraorbital artery, which provided a theoretical basis for our study.…”
Section: Discussionmentioning
confidence: 94%
“…(3) those with mental disorders; (4) those with coagulopathy; (5) those in which other treatments, such as spinal cord stimulation, trigeminal semilunar ganglion balloon compression, and traditional Chinese medicine, were used during treatment; (6) those who received other treatment options after discharge; and (7) those lost to follow-up or with incomplete data.…”
Section: Clinical Datamentioning
confidence: 99%
See 1 more Smart Citation
“…The targets for nerve block treatment in post-HZO neuralgia usually include the stellate ganglion, semilunar ganglion of the trigeminal nerve, supraorbital nerve, and terminal nerve of the frontal face. [9,13] Alternative nerve-blocking drugs comprise local anesthetics, glucocorticoids, nutraceutical drugs, ozone, and neurotropic drugs (such as doxorubicin). However, single nerve block therapy has short-lived efficacy, necessitating timely adjustments to individual treatment plans and often requiring the repetition of multiple or multi-site nerve block therapies combined with nerve regulation therapy.…”
Section: Discussionmentioning
confidence: 99%
“…[7] Some researchers have suggested the utility of the stellate ganglion, semilunar ganglion of the trigeminal nerve, [8] and its surrounding branches as therapeutic targets. [9] However, there have been no reports of combined sphenopalatine ganglion radiofrequency therapy for intractable trigeminal herpetic pain.…”
Section: Introductionmentioning
confidence: 99%